A debt crisis rooted in colonialism: a historical analysis of how the U.S.- Puerto Rico relationship contributed to Puerto Rico’s debt crisis - Perryman, Maricela (2019)
This research will explore how the colonial administration built by the United States in Puerto Rico contributed to the root causes of the debt which, I argue are a colonial- capitalist economy that developed under U.S. rule and racial subjugation of Puerto Ricans. More specifically, it will trace how the development of Puerto Rico’s institutions under U.S. colonial rule, interests of political actors, and power dynamics between the United States and Puerto Rico led to a capitalist economy on the island designed to benefit U.S. businesses, create a fragile debtor-creditor relationship, and eventually to a crippling debt crisis. I argue against the most commonly presented explanations for the debt crises by both the federal and local governments and media outlets, which are mostly around an ineffective local government with a lack of transparency and corruption. Using a postcolonial theory approach and historical institutions to place emphasis on history and institutional development over time, I analyzed critical periods of institutional change. Additionally, using discursive analysis I showed how the United States institutionalized the racialization and oppression of Puerto Rico early into their colonial rule. This research will highlight three time periods marked by what I consider to be key, influential events within the timeline of the debt crisis; the Foraker Act of 1900, the Jones Act of 1917, and the implementation of an industrialization strategy known as Operation Bootstrap in the 1940s. This research shows that that the origins of the debt crises are rooted in the history of oppression and racial subjugation within the United States-Puerto Rico colonial relationship, and that it is imperative to begin an analysis at the beginning of the U.S. installation into Puerto Rico and the discourse around the racialization of Puerto Ricans.